2020
DOI: 10.3390/nu12030741
|View full text |Cite
|
Sign up to set email alerts
|

ADORA2A C Allele Carriers Exhibit Ergogenic Responses to Caffeine Supplementation

Abstract: Caffeine’s ergogenic effects on exercise performance are generally explained by its ability to bind to adenosine receptors. ADORA2A is the gene that encodes A2A subtypes of adenosine receptors. It has been suggested that ADORA2A gene polymorphisms may be responsible for the inter-individual variations in the effects of caffeine on exercise performance. In the only study that explored the influence of variation in ADORA2A—in this case, a common polymorphism (rs5751876)—on the ergogenic effects of caffeine on ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 42 publications
(61 reference statements)
3
35
1
2
Order By: Relevance
“…Initially, three groups were created for the CYP1A2 gene (i.e., CC, CA, and AA) and for the ADORA2A gene (i.e., TT, CT, and CC). However, C-allele carriers in the CYP1A2 gene [24] and C-allele carriers in the ADORA2A gene [24,40] were clustered in the same group following previous investigations.…”
Section: Experimental Designsupporting
confidence: 57%
See 1 more Smart Citation
“…Initially, three groups were created for the CYP1A2 gene (i.e., CC, CA, and AA) and for the ADORA2A gene (i.e., TT, CT, and CC). However, C-allele carriers in the CYP1A2 gene [24] and C-allele carriers in the ADORA2A gene [24,40] were clustered in the same group following previous investigations.…”
Section: Experimental Designsupporting
confidence: 57%
“…One study reported higher improvements in TT athletes compared to C-Carriers in cycling performance [39]. However, the ergogenic response after acute caffeine intake in C-allele carriers has also been found in subsequent investigations [24,40].…”
Section: Introductionmentioning
confidence: 99%
“…Ethical approval for this study was granted by the Victoria University Human Research Ethics Committee (HRE19-019). The remaining data of the project are published elsewhere [16]. Before enrolling in the study, every participant signed an informed consent and filled out a Physical Activity Readiness Questionnaire (PAR-Q).…”
Section: Participantsmentioning
confidence: 99%
“…Establishing a cause of these divergences is not an easy task since several variables can affect HRV analysis, such as sex [33], body position [34], body mass index [35], nutritional status [36], functional condition [37], corresponding heart rate [38], cardiorespiratory fitness [39] and age [40]. In that same sense, the physiological and functional response to caffeine ingestion also depends on various factors such as individual caffeine habituation [41], caffeine dosage [42], sex [43], functional condition adopted to analysis [32], genetic profile [44], caffeine expectancies [45] and some other neuromuscular characteristics [46]. Thus, it is plausible to infer that the autonomic response to caffeine ingestion is dependent on several independent variables, and the increase of cardiac parasympathetic and global modulations observed in this study may be limited to our study design and participants' characteristics.…”
Section: Discussionmentioning
confidence: 99%